p53-loss induced prostatic epithelial cell plasticity and invasion is driven by a crosstalk with the tumor microenvironment - Darya Yanushko; Beatriz German Falcon; Rana El Bizri; Despoina Pervizou; Robin Dolgos; Céline Keime; Tao Ye; Christelle Thibault-Carpentier; Clementine Le Magnen; Sandrine Henri; Gilles Laverny; Daniel Metzger (Cell Death and Disease)
Abstract Prostate cancer is a heterogeneous disease with a slow progression and a highly variable clinical outcome. The tumor suppressor genes PTEN and TP53 are frequently mutated in prostate cancer and are predictive of early metastatic dissemination and unfavorable patient outcomes. The progression of solid tumors to metastasis is often associated with increased cell plasticity, but the complex events underlying TP53-loss-induced disease aggressiveness remain incompletely understood. Using genetically engineered mice, we show that Trp53 deficiency in Pten-null prostatic epithelial cells (PECs) does not impact early cell proliferation and neoplasia formation, nor growth arrest and senescence entry at a later time. However, Trp53-deficiency enhances invasive adenocarcinoma development and promotes metastatic cell dissemination. Importantly, our single-cell transcriptomic and chromatin accessibility analyses combined with histological examinations uncovered an epithelial cell population characterized by an induction of Jak/Stat3 signaling and displaying mesenchymal features. Moreover, we show that the transcriptomic signature of this cell population is prominent in tumors of patients with high-risk prostate cancer or metastatic disease. In addition, our in vivo and organoid-based experiments provide evidence that PEC plasticity occurs through bi-directional communication with cancer-associated fibroblasts (CAFs). Thus, our study demonstrates that p53 loss induces a protumorigenic crosstalk between PECs and CAFs, and identifies new vulnerabilities that might be targeted to limit cancer progression.